RECAA - Werkzeugunterstützung in der Anforderungserhebung - Körner, Sven J. (KIT Scientific Publishing, 2014)
Natural language is the main means to state requirements in software development. Today, requirements engineering is the first and main part of the software development and is mainly manual. These processes are error prone and depend on the experience and skills of the requirements analyst. The goal of this work is to automate parts of these manual processes with software tools.